Diagnostic Accuracy and Safety Between two Needle Sizes in Percutaneous Trans-Thoracic Biopsy for the Evaluation of Pulmonary Lesions - Yodying, Jirawadee; Sunmahakhun, Chantham; Ghimire, Pradesh; Bista, Neha (Journal of Nepal Health Research Council, 2023)
Background: Percutaneous trans-thoracic lung biopsy has a crucial role in diagnosing lung lesions including lung cancer. However, there is no clear guideline regarding the needle size in percutaneous trans-thoracic lung biopsy. This study aims to evaluate the diagnostic accuracy and complication rate between two needle sizes for percutaneous trans-thoracic lung biopsy.Methods: A retrospective review of patients with lung lesions who underwent percutaneous trans-thoracic lung biopsy between November 2010 and December 2019 was performed. The demographic data, imaging finding, biopsy technique, complication and histologic outcome were recorded and analyzed. Propensity score matching was done to reduce bias in baseline characteristics.Results: Of 377 patients who underwent percutaneous trans-thoracic lung biopsy, 331 patients had complete information. The patients were divided in two groups, comprising of 153 patients in 18G needle group and 178 patients in 20G needle group. After propensity score matching, there were 126 patients left in each group. The diagnostic accuracy, sensitivity, specificity, positive predictive value and negative predictive value for 18G needle group were 92.9%, 98.1%, 65.0%, 93.7% and 86.7%, respectively. For 20G needle group, the diagnostic accuracy, sensitivity, specificity, predictive value and negative predictive value were 96.0%, 99.0%, 83.3%, 96.2% and 95.2%, respectively. The immediate complication rate was 35.7% and 31.7% in 18G and 20 G needle groups (p= 0.505), respectively.Conclusions: There was no difference in diagnostic accuracy and immediate complication rates between 18G and 20G needle use for percutaneous trans-thoracic lung biopsy.Keywords: Complication rates; diagnostic accuracy; needle sizes; percutaneous lung biopsy; propensity score matching.